36/35-5/7-5/35=
10 1/6-(12 3/4-7 5/6)-3 1/2=
1 3/4+(99 7/20-89 2/5)-1 1/2=​


Odpowiedź :

a)

[tex] \frac{36}{35} - \frac{5}{7} - \frac{5}{35} = \frac{36}{35} - \frac{25}{35} - \frac{5}{35} = \frac{6}{35} [/tex]

b)

[tex]10 \frac{1}{6} - (12 \frac{3}{4} - 7 \frac{5}{6} ) - 3 \frac{1}{2} = 10 \frac{2}{12} - (12 \frac{9}{12} - 7 \frac{10}{12} ) - 3 \frac{6}{12} = 10 \frac{2}{12} - (11 \frac{21}{12} - 7 \frac{10}{12} ) - 3 \frac{6}{12} = 10 \frac{2}{12} - 4 \frac{11}{12} - 3 \frac{6}{12} = 9 \frac{14}{12} - 4 \frac{11}{12} - 3 \frac{6}{12} = 5 \frac{3}{12} - 3 \frac{6}{12} = 4 \frac{15}{12} - 3 \frac{6}{12} = 1 \frac{9}{12} = 1 \frac{3}{4} [/tex]

c)

[tex]1 \frac{3}{4} + (99 \frac{7}{20} - 89 \frac{2}{5} ) - 1 \frac{1}{2} = 1 \frac{15}{20} + (99 \frac{7}{20} - 89 \frac{8}{20} ) - 1 \frac{10}{20} = 1 \frac{15}{20} + (98 \frac{27}{20} - 89 \frac{8}{20} ) - 1 \frac{10}{20} = 1 \frac{15}{20} + 9 \frac{19}{20} - 1 \frac{10}{20} = 10 \frac{34}{20} - 1 \frac{10}{20} = 9 \frac{24}{20} = 10 \frac{4}{20} = 10 \frac{1}{5} [/tex]

Myślę że pomogłem ;)